2022
DOI: 10.1002/cam4.4648
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 testing among young women with breast cancer in Massachusetts, 2010–2013: An observational study using state cancer registry and All‐Payer claims data

Abstract: Background Testing for BRCA1/2 pathogenic variants is recommended for women aged ≤45 years with breast cancer. Some studies have found racial/ethnic and socioeconomic disparities in testing. We linked Massachusetts' All‐Payer Claims Database with Massachusetts Cancer Registry data to assess factors associated with BRCA1/2 testing among young women with breast cancer in Massachusetts, a state with high levels of access to care and equitable insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Risk for breast cancer increases with mutations in the BRCA1/2 genes, so identifying women with these mutations ideally spurs risk management actions [ 19 ]. Recent research has shown that Black women under age 50 had lower odds of undergoing BRCA1/2 testing after a breast cancer diagnosis compared to White women [ 20 , 21 ]. This disparity likely contributes to the higher breast cancer mortality rates among Black women.…”
Section: Discussionmentioning
confidence: 99%
“…Risk for breast cancer increases with mutations in the BRCA1/2 genes, so identifying women with these mutations ideally spurs risk management actions [ 19 ]. Recent research has shown that Black women under age 50 had lower odds of undergoing BRCA1/2 testing after a breast cancer diagnosis compared to White women [ 20 , 21 ]. This disparity likely contributes to the higher breast cancer mortality rates among Black women.…”
Section: Discussionmentioning
confidence: 99%